Increase in gamma/delta T cell receptor bearing lymphocytes in normal small bowel mucosa in latent coeliac disease. Issue 11 (November 1991) - Mäki, M; Holm, K; Collin, P; Savilahti, E
Abstract : A jejunal biopsy specimen from an asymptomatic 35 year old man was studied because of a low serum titre of reticulin antibody and the finding of coeliac disease in his son. In this specimen villous structure was quite normal as was the total number of intraepithelial lymphocytes, but the number of gamma/delta T cell receptor bearing lymphocytes was 10 times higher than the mean in control subjects. Two years later a further biopsy specimen was obtained because of clinical symptoms and an increased titre of reticulin antibody. This specimen showed villous atrophy with crypt hyperplasia and increased infiltration of intraepithelial lymphocytes compatible with coeliac disease. A control biopsy specimen taken during gluten free diet showed normalisation of the villous architecture. Latent coeliac disease may be characterised by an increase in gamma/delta positive cells similar to that seen in established coeliac disease.